Pengaruh Literasi Keuangan, Pemanfaatan Sistem Informasi Akuntansi Dan Penggunaan Teknologi Informasi Terhadap Kinerja UMKM - Kiki Rizkiya Amalia Lubis; Rohma Septiawati; Ihsan Nasihin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Micro, Small and Medium Enterprises (SMEs) are important in the economic growth of a country. In recent years, UMKM at Karawang Base has faced various challenges and changes including low financial literacy, lack of understanding of basic financial concepts such as budget, investment, and long-term planning. difficulty adopting information technology due to limited access and limited understanding of its benefits to operational efficiency and marketing. UMKM's financial management is inefficient, including the difficulty of compiling accurate and regular financial reports, hindering proper analysis and decision-making. Using accounting information systems is important in improving UMKM performance, helping to collect, manage, and analyze financial data efficiently. This research is done using quantitative methods. The sample consisted of 249 UMKMs at Karawang Base District, which were selected through purposive sampling. SmartPLS software is used to test research data using structural equation models. The results of this study concluded that Financial Literacy had no significant impact on UMKM performance with P values 0.103, whereas Information Systems and Accounting Information System Usage had a positive and significant impact with P Values 0,000. Keywords: Financial literacy, UMKM performance, accounting information systems, use of information technology